Phraseologisms and Their Significance in the Child's Language Enrichment - Kuzina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article reflects on the richness of Latvian phraseologisms, their usage for enriching of the child's language; it provides an analyses of RPIVA students' survey and results of tests and tasks done by the learners of Forms 4,7 and 9 of Pumpuri Secondary School, which are connected with the assessment of students' knowledge of phraseologisms.Each nation possesses its own amount of phraseologisms or phraseology. Without knowledge of the phraseologisms it is difficult to understand precisely the respective language. Therefore, while learning a language, a peculiar attention should be paid to its phraseology. Phraseologisms most often are encountered in conversational language, folklore and in peculiar language used by fiction characters. They make the language more vital, expressive, inspirational and the narration – appears more emotional, dexterious and witty. Researches reveal that modern learners get scarce insight into phraseologisms and their usage. Thus, both – pupils and students' knowledge of them is insufficient, hence, they are unable to use them adequately in Latvian. By teaching of phraseologisms and their usage both in verbal and written texts' acquisition, the pupils vocabulary is advanced and enriched properly.